Interoperability architecture for bridging computational tools: application to steel corrosion in concrete. (15th January 2020) - Mir, Zahid M; Friis, Jesper; Hagelien, Thomas F; Svenum, Ingeborg-Helene; G Ringdalen, Inga; Konchakova, Natalia; Zheludkevich, Mikhail L; Höche, Daniel
Abstract: A multiscale modelling framework, especially for corrosion modelling, requires not only robust computational tools but also an efficient datacentric architecture for handling information exchange at different modelling scales. Different computational solvers require and produce data in different programming languages and specific formats signifying a strong non-uniformity for an easy nexus with other solvers. This non-uniformity has created a need to focus on intermittent state-of-the-art datacentric software tools which aim to bridge data exchange heterogeneity across diverse set of solvers. Data organization in the form of metadata structures are presented as a standard for a coherent information representation regardless of the diverse nature of data formats specific to a scientific discipline. This fundamental work presents the concept, underlying terminology and working mechanism of a datacentric architecture tool SOFT5 for exchanging and interfacing data-flow between solvers and its present application to a concrete technology multiscale simulation network as a potential application.